Combined conchal cartilage islet-periosteum and posterior based pedicled flap obliteration: a comparison with unobliterated mastoid cavities - Das, Arindam; Mitra, Sandipta; Hazra, Sayan; Sengupta, Arunabha (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Aim of the study was to compare the outcomes of a new technique of mastoid cavity obliteration with open mastoid cavity. Methods: 90 patients diagnosed with chronic otitis media (active squamosal variety) and planned to undergo surgery between 2016-2018 were randomly assigned into two groups of 45 patients. One group underwent canal wall down matoidectomy followed by cavity obliteration with posteriorly based vascularised flap with mastoid cortex periosteum plus conchal cartilage composite graft and the other underwent the same surgery but without any obliteration. The two groups were compared in terms of cavity volume, discharge, epithelisation, wax formation, subjective sensation of vertigo and post-operative air-bone gap at 1 year. Results: Cavity obliteration in post-canal wall down setting significantly reduced the post-operative cavity volume and need for cavity debridement with better epithelisation, less incidence of discharge, vertigo on caloric stimulation when compared to open cavity. The post-operative air-bone gap in obliterated cavities was better but not statistically significant. Conclusion: Cavity obliteration has definite advantages over open cavity in terms of healing but no significant differences in long-term audiological outcomes.